Spillover effects of the recent US monetary policy shocks on the South African economy: The role of monetary and fiscal policy coordination - Guangling Liu; Marrium Mustapher (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study examines how different policy mix regimes affect the impact of recent US contractionary monetary policy on South Africa's inflation and business cycles. The study uses a small open economy New Keynesian Dynamic Stochastic General Equilibrium model with an integrated fiscal block to analyse these effects. Regime M (active monetary policy) is more effective at containing the spillover effects but leads to higher public debt, requiring larger future fiscal surpluses. The commitment to price stability under Regime M increases real interest rates, raising domestic debt service costs and the debt-to-GDP ratio. Regime F (active fiscal policy), in contrast, stabilizes debt more quickly but at the cost of higher inflation, as it does not use future surpluses to manage public debt. These spillover effects are more amplified under both Regime M and Regime F in the case of a complete exchange rate pass-through and a higher degree of trade openness, with Regime F exhibiting a stronger amplification effect.
Keywords: E3; E5; E6; E12; 330; foreign monetary policy; monetary and fiscal policy coordination; New Keynesian Dynamic Stochastic General Equilibrium; policy spillovers; small open economy